Pengaruh Model Make a Match Terhadap Hasil Belajar IPAS Kelas V SD 3 Peganjaran Kudus - Rohmah, Anisatur; Ratnasari , Yuni; Suhartati, Oktri; Ikhtiarto, Fit Pipin (Universitas Tidar, 2025)
This research aims to determine the effect of implementing the model make a match on the learning outcomes of Natural and Social Sciences (IPAS) class V SD 3 Peganjaran Kudus. The type of research used is Classroom Action Research (PTK) using the Kemmis and McTaggart model which is carried out in two cycles, each cycle being carried out in three meetings. Data collection techniques use tests, observation and documentation. The data analysis technique used is a quantitative descriptive technique. The subjects of this research were 18 class V students at SD 3 Peganjaran Kudus. This research was conducted in the even semester of the 2024/2025 academic year, precisely in January and February. In the pre-cycle stage it is carried out pre-test and showed that only 5 students achieved the minimum completeness criteria (KKM) score of 70 and 13 students scored below the KKM with an average score of 39. The research results showed: in cycle I, 9 students did not complete (50%) and 9 students completed (50%) with an average score of 54, and in cycle II there were 2 students who completed (11%) and 16 students complete (89%) with an average score of 83. So the model is used Make a Match can improve the science and science learning outcomes of class V students at SD 3 Peganjaran Kudus in the second semester of the 2024/2025 academic year.